The role of management information systems on the organizational culture of employees: A case study of Faisal Islamic Bank of Sudan - Mudwi, Sara Suliman Alawad; Mohamed, Reda Abdelfattah Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the impact of the requirements of management information systems (physical, network, and human) as an independent variable and the elements of organizational culture (values, attitudes) as a dependent variable. The study relied on the analytical descriptive approach and case study. The study population consisted of (360) employees of Faisal Islamic Bank. The soft probability sampling method was used, and the study relied on the questionnaire as a main tool in data collection. (189) questionnaires were distributed and (160) valid for analysis were retrieved, with a rate of (84.6%), Descriptive statistics (median, standard deviation, correlation) and analytical statistics (exploratory and confirmatory factor analysis and path analysis) were used. The results of the study revealed that there is a significant positive relationship between the requirements of management information systems (physical, networked, and human) and the organizational values ​​of culture. While there is no positive and significant relationship with organizational trends of culture. The study recommended the necessity of continuing to raise the competencies of the components of management information systems and maintaining a positive and moral level of organizational culture, It also recommended the need to apply the studies in other environments with different technical and organizational dimensions.